1993
DOI: 10.1128/jb.175.4.1206-1210.1993
|View full text |Cite
|
Sign up to set email alerts
|

Noninducible Tet repressor mutations map from the operator binding motif to the C terminus

Abstract: We have developed a new genetic selection system for Tet repressor mutations with a noninducible phenotype for tetracycline (TetRs). Extensive chemical mutagenesis of tetR yielded 93 single-site Tet repressor mutations. They map from residue 23 preceding the a-helix-turn-a-helix operator binding motif to residue 196 close to the C terminus of the repressor. Thirty-three of the mutations are clustered between residues 95 and 117, and another 27 are clustered between residues 131 to 158. Several of the mutants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 20 publications
7
55
0
Order By: Relevance
“…The results of a large number of biochemical, structural, and mutagenesis studies on TetR(B) and TetR(D) are in good agreement, which provides an exceptionally detailed picture of the induction process (55,60,135,193,194,205). In addition to identifying amino acids involved in the induction process, random mutagenesis has even produced a TetR mutant that exhibits increased, not decreased, affinity for the tet operator upon inducer binding, which, in combination with the relative nontoxicity of tetracycline to eukaryotic cells, has facilitated its use to tightly regulate gene expression in eukaryotes (16,44,62).…”
Section: Tetr-ligand Interactionssupporting
confidence: 51%
“…The results of a large number of biochemical, structural, and mutagenesis studies on TetR(B) and TetR(D) are in good agreement, which provides an exceptionally detailed picture of the induction process (55,60,135,193,194,205). In addition to identifying amino acids involved in the induction process, random mutagenesis has even produced a TetR mutant that exhibits increased, not decreased, affinity for the tet operator upon inducer binding, which, in combination with the relative nontoxicity of tetracycline to eukaryotic cells, has facilitated its use to tightly regulate gene expression in eukaryotes (16,44,62).…”
Section: Tetr-ligand Interactionssupporting
confidence: 51%
“…A possible explanation is that multiple mutations may be required in PmtaC1 to result in a deregulated but still active promoter. On the other hand, a single point mutation can render a regulatory protein unable to bind its target site (16). It should be noted that proteins other than a transcriptional regulator, regulatory RNA, or metabolites, which might interact with DNA sequences and/or components of the transcription machinery, could be affected by the mutation observed.…”
Section: Discussionmentioning
confidence: 99%
“…1). Deletion mutagenesis analyses of the TetR protein have shown that the residues needed for the activity of the repressor are distributed all along the protein sequence (6,7,18,37,41). The N-terminal region contains the DNA-binding domain; and the C-terminal region contains the dimerization domain, the region required for the binding of tetracycline, and regions involved in the folding and stability of the protein.…”
Section: Discussionmentioning
confidence: 99%